Roles of human papillomaviruses and p16 in oral cancer - Thanun Sritippho (2018)
Head and neck cancer, including oral cancer, is the sixth most common cancer in humans worldwide. More than 90% of oral cancers are of squamous cell carcinoma type. Recent studies have shown a strong relationship between human papillomavirus (HPV) infection and head and neck cancer, especially oropharyngeal squamous cell carcinoma (OPSCC) and oral squamous cell carcinoma (OSCC). Moreover, the incidence of HPV-related OSCC appears to be on the rise while HPV-unrelated OSCC tends to have stabilized in the past decades. p16, a tumor suppressor gene, normally functions as a regulator of the cell cycle. Upon infection with high-risk types of HPV (HR-HPV), particularly types 16, 18, 31, 33, 34, 35, 39, 51, 52, 56, 58, 59, 66, 68, and 70, the expression of p16 is aberrantly overexpressed. Therefore, the expression of p16 is widely used as a surrogate marker for HPV infection in head and neck cancer.